Exploring the interplay between protein conformational changes and phosphorylation in a pancreatic cancer cell and stellate cell coculture system - Haiyan Lu; Yuan Liu; Hung-Yu Chiang; Hua Zhang; Xudong Shi; Lingjun Li (Proceedings of the National Academy of Sciences, 2026)
A global exploration of the complex interplay between protein conformational changes and phosphorylation events in cell–cell interactions is crucial for understanding the dynamic nature of protein modifications. This understanding is essential for developing novel targeted therapies for pancreatic cancer, particularly in the context of interactions between pancreatic cancer cells (PCCs) and pancreatic stellate cells (PSCs). However, protein conformational changes that occur during PCCs–PSCs interactions remain poorly studied, and the relationship between these changes and phosphorylation is not well understood. Here, we present a comprehensive mass spectrometry–based study investigating the interplay between protein conformational alterations and phosphorylation in a coculture system of pancreatic ductal adenocarcinoma cells (PANC-1) and PSCs. Our results demonstrate that 435 proteins exhibiting conformational changes were detected during the coculture of PANC-1 with PSCs, primarily involving proteins associated with the tricarboxylic acid (TCA) cycle, glycolysis/gluconeogenesis, and carbon metabolism. Our findings also highlight a potential association between phosphorylation and protein conformational changes. Moreover, we identified five potential conformational targets, including ACLY, ACO1, ACO2, IDH1, and OGDH, which may provide valuable insights into the molecular pathways underlying gemcitabine resistance in pancreatic cancer. Overall, these results offer insights into protein conformational changes and their potential link to phosphorylation in the context of cancer-stromal cell interactions, paving the way for structure-based, targeted therapeutic strategies for pancreatic cancer treatment.